Mathematical Modelling and Computer Simulation of Human Locomotion - Pal, George Thomas (My University, 1978)
This study is a theoretical investigation of the process of human locomotion. It is restricted to the lower limbs and includes the major muscles of the legs.
A mathematical model is presented incorporating some of the findings of earlier investigators of locomotion dynamics and of muscular control. The underlying hypothesis is that locomotion is an optimal control process governed by a minimum energy condition. Pontryagin's Maximum Principle is used to implement this optimality criterion. The model is then programmed for evaluation on a high speed digital computer.
The results of the computer simulation are presented along with experimental verification of the findings. The close agreement between the two suggests that the model is an analytical tool that may be used as a foundation for programs of Functional Electro-Stimulation as aids for the physically handicapped.
Included are further suggestions regarding the application of the model to other biomedical problems as well as recommendations for extensions of the work to broaden the scope of utility.
Keywords: Mechanical Engineering; Mechanical Engineering